HUMAN SECURITY DALAM NEGARA DEMOKRASI: PERSPEKTIF MEDIA STUDIES - Kazan Gunawan (Jurnal Kawistara, 2011)
The aim of this article is to explain the relation between human security and media studies when looking at the problem of security in Indonesia, a country experiencing a process of  democratization. In media studies, the problem of human security often only emphasizes discourse and event analysis, without relating it with the human security problem. Connecting human security and media is very important because media has a very important role in constructing the public and State’s opinion. This article analyses news, as reported in the media, then gives context about the State and problems related to human security. It is concluded that media is highly influential in studying human security because of its numerous economic, political and cultural interests.